Outcomes of hospital-acquired SARS-CoV-2 infection in the Canadian first wave epicentre: a retrospective cohort study - Melançon, Eve; Brosseau, Marc; Bartoli, Anthony; Labbé, Annie-Claude; Lavallée, Christian; Marchand-Senécal, Xavier; Wang, Han Ting (CMAJ Open, 2022)
Background: During the first wave of the COVID-19 pandemic, a substantial number of Quebec hospitals were hit by hospital-acquired (HA) SARS-CoV-2 infections. Our objective was to assess whether mortality is higher in HA cases than in non-hospital-acquired (NHA) cases and determine the prevalence of HA-SARS-CoV-2 infection in our hospital.Methods: This retrospective single-centre cohort study included all adults (≥ 18 yr) who had COVID-19, admitted to Hôpital Maisonneuve-Rosemont (Montréal, Canada) from Mar. 1 to June 30, 2020. We collected data on demographic characteristics, comorbidities, treatment, admission to the intensive care unit (ICU) and mechanical ventilation requirements from electronic health records. We adjudicated hospital acquisition based on the timing of symptom onset, and polymerase chain reaction testing for and exposures to SARS-CoV-2. To evaluate the association between HA-SARS-CoV-2 infection and in-hospital mortality, we computed a multivariable logistic regression analysis including known risk factors for death in patients with COVID-19 as covariates.Results: Among 697 patients with SARS-CoV-2 infection, 253 (36.3%) were classified as HA. The mortality rate was higher in the HA group than in the NHA group (39.1% v. 25.9%, p = 0.001), while the rates of ICU admission (8.3% v. 19.1%, p = 0.001) and requirement for mechanical ventilation (3.6% v. 13.0%, p = 0.001) were lower. Multivariable logistic regression analysis showed that HA-SARS-CoV-2 infection in patients younger than 75 years is an independent risk factor for death (odds ratio 2.78, 95% confidence interval 1.44–5.38).Interpretation: Our results show that HA-SARS-CoV-2 infection in younger patients was associated with higher mortality. Future studies need to evaluate relevant patient-centred long-term outcomes in this population.